Ecology and drivers of decline in a tropical island honeyeater : the Ma'oma'o : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Zoology at Massey University, Manawatu, New Zealand - Stirnemann, Rebecca (Massey University, 2015)
There is a worldwide decline in biodiversity. Few studies have explored the processes that underlie biodiversity decline in some tropical regions, especially on tropical oceanic islands, where there are many threatened species and a high level of endemism. Indeed, even basic biological information is lacking for many Oceanic species. The Ma’oma’o (Gymnomyza samoensis), an endangered honeyeater endemic to Samoa, is an example of this. Here, I report results from an investigation on: 1) the breeding biology of this island honeyeater, 2) how survival varies with life history stage, 3) how to sex this monomorphic species in the field, and 4) how landscape and local-scale vegetation features influence nest predation of these cup nesting birds. I used observational data on breeding biology and survival at different life history stages to determine why this species is declining, and a combination of vegetation mapping and artificial nest surveys to determine how landscape processes and predation by invasive species contribute to declines in Oceanic forest birds. I also collected morphometric measurements and calls of known-sex individuals to develop a method of sexing Ma’oma’o in the field and to assess whether the declining populations showed sex bias. I found that the decline of this species is driven by interactions between the life history traits, predation by the black/ship rat (Rattus rattus), and fine and large-scale vegetation and landscape attributes. The Ma’oma’o produces at most one chick per year and therefore has a small maximum annual reproductive success rate compared to other honeyeaters. Furthermore, compared to other honeyeaters, the Ma’oma’o remains in the nest for longer and has an extended fledgling dependency period. My study highlights how predation by black rats at the nest reduces reproductive success. I found that the probability of nest success was significantly reduced near plantations. However, interior forest did not have lower nest predation rates then edge forest. My findings indicate that the maintenance of large sections interior forest alone is unlikely to increase reproductive success for the Ma’oma’o or indeed for other forest bird species sensitive to black rat predation. The key management strategy is to have intensive rat control at breeding sites during the reproductive season.
Keywords: Honeyeaters; Ma'oma'o; Gymnomyza samoensis; Conservation; Samoan Islands; Samoa